Penerapan Konseling Individual dengan Teknik Rasional Emotif Behavior untuk Mengatasi School Refusal Pada Santriwati (Studi Kasus Klien “R” di Pondok Pesantren Sabilul Muhtadin) - Eka Fitria; Abdur Razzaq; Emi Puspita Dewi (Berkala Ilmiah Pendidikan, 2024)
School refusal is school refusal behavior that is motivated by unwillingness to attend school or finding it difficult to stay at school all day. This research aims to determine the description of school refusal in client "R" at the Sabillul Muhtadin Islamic Boarding School. To determine the application of individual counseling rational emotive behavior techniques to overcome school refusal in client "R" female students at the Sabillul Muhtadin Islamic Boarding School. This research uses a qualitative approach method with a case study type of research. The data collection techniques use observation, interviews and documentation methods. Meanwhile, the data analysis technique used is done by pattern matching, data explanation, and time series analysis. The results of this research show that the school refusal experienced by client "R" has two factors, namely the internal factor of the client experiencing separation anxiety from their parents (separation anxiety) and the external factor, namely school being unpleasant or creating an unsafe condition for the client. After counseling using rational emotive behavioral therapy (REBT) techniques for client "R", there was some progress felt by client "R" after carrying out the counseling guidance process for client "R", starting to decrease in doing things that made client "R" skipping class, starting to take part in learning activities at school and getting rid of the irrational feelings he had been feeling, client "R" began to think rationally towards the people in his environment and began to have the courage to fight the fear and anxiety that was occurring within him.